Developing and maintaining a design-tech portfolio : a guide for theatre, film and TV - Jaen, Rafael (Focal Press, 2006)
This book is a practical guide to aid in the process of creating, developing and presenting successful Theatre/TV/Film design/technology portfolios in the fields of scenery, costumes, lighting and sound. The book will consist of four sections or chapters. The first section is dedicated to the realization of effective portfolio showcases and it will identify materials and techniques used to produce them. This chapter will also identify specific requirements by discipline including scenery, costumes, lighting and sound and will cover the different portfolio requirements to apply for graduate school, jobs in the field, professional organizations and for promotional purposes. The second section is dedicated to the development and use of digital portfolios and it will look at the different software used in this area. The third chapter is about presentation and marketing and it will describe how to develop personal presentation techniques, resume, business card, and web pages. Finally, the fourth section offers key information in regards to the maintenance and updating of portfolios. Each chapter will feature real samples from the professional field and a page of "do's and don'ts" with comments from experts in each design-tech discipline. * Contains specific guidelines about work layout techniques for Design and Technology Portfolios (for Theatre, Film and TV) * Added comments (do's and don'ts) from many professionals in the field as well as tips on personal presentation during (job and/or college) interviews * Includes detail lists of recommended best supplies to put a portfolio together and vendor sources.